mTOR inhibition as an adjuvant therapy in a metastatic model of HPV+ HNSCC - Coppock, Joseph D. (Oncotarget, 2016)
Effective treatments for recurrent/metastatic human papillomavirus-positive (HPV+) head and neck squamous cell cancer (HNSCC) are limited. To aid treatment development, we characterized a novel murine model of recurrent/metastatic HPV+ HNSCC. Further analysis of the parental tumor cell line and its four recurrent/metastatic derivatives led to preclinical testing of an effective treatment option for this otherwise fatal disease. Reverse phase protein arrays identified key signaling cascades in the parental and recurrent/metastatic cell lines. While protein expression profiles differed among the recurrent/metastatic cell lines, activated proteins associated with the mTOR signaling cascade were a commonality. Based on these data, mTOR inhibition was evaluated as an adjuvant treatment for recurrent/metastatic disease. mTOR activity and treatment response were assessed in vitro by western blot, Seahorse, proliferation, clonogenic, and migration assays. Standard-of-care cisplatin/radiation therapy (CRT) versus CRT/rapamycin were compared in vivo. Low-dose rapamycin inhibited mTOR signaling, decreasing proliferation (43%) and migration (62%) while it enhanced CRT-induced cytotoxicity (3.3 fold) in clonogenic assays. Furthermore, rapamycin re-sensitized CRT-resistant, metastatic tumors to treatment in vivo, improving long-term cures (0–30% improved to 78–100%, depending on the recurrent/metastatic cell line) and limiting lymph node metastasis (32%) and lung metastatic burden (30 fold). Studies using immune compromised mice suggested rapamycin's effect on metastasis is independent of the adaptive immune response. These data suggest a role of mTOR activation in HPV+ HNSCC recurrent/metastatic disease and that adjuvant mTOR inhibition may enhance treatment of resistant, metastatic cell populations at the primary site and limit distant metastasis.